Retroperitoneal Müllerian cyst causing uterine protrusion in a teenage girl - Fu-Chieh Chu; Hsu-Han Wang; Yen-Tin Chen; Ya-Chun Chuang; Liang-Ming Lo; Steven W. Shaw (Taiwanese Journal of Obstetrics & Gynecology)
Objective: To describe a rare case of a retroperitoneal Müllerian cyst in a teenage girl with a protruding uterus and associated urogenital anomalies, and to discuss the challenges faced in differential diagnosis and management of such cases. Case report: We present the case of a 14-year-old girl presented with a protruding uterus for several weeks, with a history of twin–twin transfusion syndrome at birth. Initial ultrasonography identified a large pelvic cystic tumor. Notably, during laparoscopy, a significant left retroperitoneal tubulocystic tumor was discovered, and the left ureter was absent. A computed tomography scan confirmed left renal agenesis, right kidney hyperplasia, a bicornuate uterus, and pectus excavatum. Surgical exploration and excision of the tumor were performed, with histological and immunohistochemical analyses confirming the presence of a Müllerian-type epithelium. Post-surgery, the protruding uterus improved, and the patient demonstrated notable recovery at a six-month follow-up. Conclusion: Retroperitoneal Müllerian cysts, though rare, should be considered in differential diagnoses of retroperitoneal cystic tumors, especially in patients with associated urogenital anomalies. Immunohistochemical profiling plays a critical role in distinguishing Müllerian cysts from other urogenital cysts. Patients with renal anomalies should be evaluated for associated urogenital anomalies, and surgical intervention should be considered based on symptom presentation and potential for malignancy.